Cross-border effects of prudential regulation: Evidence from the euro area - Franch, Fabio; Nocciola, Luca; Żochowski, Dawid (Journal of Financial Stability, 2021)
Using the Prudential Instruments Database (Cerutti et al., 2017b) and a unique confidential database on balance sheet items of euro area financial institutions, we analyse cross-border spillovers from prudential regulation for 248 banks from 16 euro-area countries over the period 2007Q3–2014Q4. We find that foreign branches increase lending following the tightening of sector-specific capital buffers, loan-to-value (LTV) limits or reserve requirements on deposits in local currencies in the countries where their parent banks reside. We also find that cross-border spillovers through lending of branches are stronger than through subsidiaries, possibly because it is easier for branches to reallocate lending across different jurisdictions, as they do not need to meet prudential requirements at a solo level. Finally, we find that also euro-area domestic banks increase lending, in particular to the real sector, when LTV limits are tightened abroad.